Deicing Salt Pollution Affects the Foliar Traits and Arthropods' Biodiversity of Lime Trees in Riga's Street Greeneries - Bouraoui, Dalinda; Cekstere, Gunta; Osvalde, Anita; Vollenweider, Pierre; Rasmann, Sergio (Frontiers in Ecology and Evolution, 2019)
Street greeneries and other green spaces within the urban matrix can potentially reduce air pollution and increase urban biodiversity. Yet, these services can be negatively affected by anthropogenic stress factors. In the boreo-nemoral zone, large amounts of salts are spread each year for deicing the pavement. To address the effect of deicing salt on street lines of lime trees and how this cascades up to influence the surrounding arthropod biodiversity, we compared heavily salt-polluted and less polluted sites in the city of Riga, Latvia. We analyzed the impairment of foliar functions and development of aphids’ colonies using a common garden experiment. We found marked variation in the soil physico-chemical properties in polluted versus unpolluted sites. The overall abundance of arthropods, including that of the lime tree aphid specialist, was decreased and, as a consequence, less biotic injury was observed in foliage. The exposure to increased salt levels in the soil caused functional as well as structural injuries within foliage and slowed down the development of aphid colonies. The effects of de-icing salts thus appeared to cascade up through the trophic chain and to negatively affect not only the trees but also the associated arthropod biota. These findings point at the necessity of a wider screening of plant species and cultivars that not only better tolerate anthropogenic stress but also promote the biodiversity in cities.